(untitled) (Prilozi za orijentalnu filologiju, 2024)
The highest representative of the judicial authority and one of the most im- portant levers in the administrative apparatus of the Ottoman Empire in one province (eyalet) was the molla. He was granted extensive powers and the ability to control other officials of the Ottoman authority. Considering the role and importance of those high-ranking Ottoman officials, the paper aims to present the individuals who were appointed to the Eyalet of Bosna as well as the dynamics of changes in these positions in the second half of the 17th century. In cases where it was possible, insight was given into their education and experience, as well as some interesting facts from their lives. In order to achieve this, the contents of various individual and collective documents were analyzed. The presented data contribute to a better understanding of Ottoman judicial practice and the specific activities of judges in Bosnia in the 17th century.